Cardiovascular and renal outcomes of glucagon-like peptide 1 receptor agonists among patients with and without type 2 diabetes mellitus: A meta-analysis of randomized placebo-controlled trials - Frederick Berro Rivera; Linnaeus Louisse A. Cruz; John Vincent Magalong; Jade Monica Marie J. Ruyeras; John Paul Aparece; Nathan Ross B. Bantayan; Kyla Lara-Breitinger; Martha Gulati (Elsevier, 2024)
Background: Multiple cardiovascular outcomes trials (CVOTs) have shown the efficacy of GLP-1RAs in reducing major adverse cardiovascular events (MACEs) for high-risk patients. However, some CVOTs failed to demonstrate cardiovascular benefits. Objectives: We analyzed the impact of GLP-1RA on cardiovascular and renal outcomes in patients with or without T2DM, with subgroup analysis based on sex, estimated glomerular filtration rate (eGFR), body mass index (BMI), and history of cardiovascular disease (CVD). Methods: A comprehensive database search for placebo-controlled RCTs on GLP-1RA treatment was conducted until April 2024. Data extraction and quality assessment were carried out, employing a robust statistical analysis using a random effects model to determine outcomes with log odds ratios and 95 % confidence intervals (CIs). Results: A total of 13 CVOTs comprising 83,258 patients were included. GLP-1RAs significantly reduced MACE (OR 0.86, 95 % CI: 0.80 to 0.94, p < 0.01) all-cause mortality OR 0.87, 95 % CI: 0.82 to 0.93, p < 0.001, CV mortality (OR 0.87, 95 % CI: 0.81 to 0.94, p < 0.001), stroke (fatal: OR 0.74, 95 % CI: 0.56 to 0.96, p = 0.03; non-fatal: OR 0.87, 95 % CI: 0.79 to 0.96, p = 0.005), coronary revascularization (OR 0.86, 95 % CI: 0.74 to 0.99, p = 0.023), and composite kidney outcome (OR 0.76, 95 % CI: 0.67 to 0.85, p < 0.001. GLP-1RA significantly reduced MACE in both sexes. Furthermore, GLP-1RA reduced MACE regardless of CVD history, BMI, and eGFR level. Conclusion: Significant reductions in MACE, overall and CV mortality, stroke, coronary revascularization, and composite kidney outcome with GLP-1RA treatment were noted across all subgroups.